50th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2012
DOI: 10.2514/6.2012-832
|View full text |Cite
|
Sign up to set email alerts
|

Code Development of Linearized Euler Equation on Block-Structured Cartesian Mesh for Complicated Geometries

Abstract: The Linearized Euler Equation code for aeroacoustic analysis has been developed on block-structured Cartesian mesh to treat the complicated geometries robustly and accurately. In the present method, spatial derivation and time integration are conducted by high order schemes and the immersed boundary method using ghost cell approach is employed at the wall boundary. At the block boundary, higher-order data exchange is conducted by Lagrange interpolation and near the outer boundary outgoing wave is damped by abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Here, the vorticity magnitude is considered as the characteristic value i in Equation (2). The large value of gives small quantization step size in Equation (6), and small error as shown in Figure 7(b). The contour lines from the compressed data and the original data represent similar features, which means that the compressed data can preserve a complex wake flow structure behind the sphere.…”
Section: Compression Of Flow Simulation Data Set Past a Spherementioning
confidence: 99%
See 3 more Smart Citations
“…Here, the vorticity magnitude is considered as the characteristic value i in Equation (2). The large value of gives small quantization step size in Equation (6), and small error as shown in Figure 7(b). The contour lines from the compressed data and the original data represent similar features, which means that the compressed data can preserve a complex wake flow structure behind the sphere.…”
Section: Compression Of Flow Simulation Data Set Past a Spherementioning
confidence: 99%
“…Here, it is shown that the value of in Equation (2) is large in the wake region (Figure 7(a)), where strong vortices exist. The large value of gives small quantization step size in Equation (6), and small error as shown in Figure 7(b). This results in a good preservation property for the characteristic vortex structure.…”
Section: Compression Of Flow Simulation Data Set Past a Spherementioning
confidence: 99%
See 2 more Smart Citations